PENGARUH E-COMMERCE, PENGETAHUAN AKUNTANSI DAN BUDAYA ORGANISASI TERHADAP KINERJA UMKM DI KOTA MALANG - Enis Setiawati; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This research was conducted to determine the effect of E-Commerce, Accounting Knowledge and Organizational Culture on the Performance of Micro, Small and Medium Enterprises in Malang. The method used is explanatory research. It is a research method that intends to explain the position of the variables studied and the influence between one variable. with other variables, and the data source used is primary data, namely by distributing linkert scale questionnaires to owners / managers of Micro, Small and Medium Enterprises in Malang City. The sample calculation in this study used the Slovin formula which resulted in 99 respondents. The results of this study are the variables of e-commerce, accounting knowledge and organizational culture have a simultaneous and partial effect on the performance of micro, small and medium enterprisesKeywords: The influence of e-commerce, accounting knowledge and organizational culture and the performance of Micro, Small and Medium Enterprises